2009
DOI: 10.1371/journal.pntd.0000427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Five-Year Citywide Intervention Program To Control Aedes aegypti and Prevent Dengue Outbreaks in Northern Argentina

Abstract: BackgroundDengue has propagated widely through the Americas. Most countries have not been able to maintain permanent larval mosquito control programs, and the long-term effects of control actions have rarely been documented.MethodologyThe study design was based on a before-and-after citywide assessment of Aedes aegypti larval indices and the reported incidence of dengue in Clorinda, northeastern Argentina, over 2003–2007. Interventions were mainly based on focal treatment with larvicides of every mosquito deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 41 publications
(54 reference statements)
3
78
0
1
Order By: Relevance
“…In the remaining studies [20], [32], [33], [41], [42] a variety of mixed, inconclusive or weak associations were reported. Gurtler et al conducted analyses on the effect of a given intervention on mosquito indices but not on dengue cases [32].…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining studies [20], [32], [33], [41], [42] a variety of mixed, inconclusive or weak associations were reported. Gurtler et al conducted analyses on the effect of a given intervention on mosquito indices but not on dengue cases [32].…”
Section: Resultsmentioning
confidence: 99%
“…For example, larvae and pupae productivity was not evaluated and stringent quantitative analysis to explore the implications of this factor in terms of larvae and pupae productivity is recommended. Closed or refused premises have also been a frequent limitation in previous studies 5 . Although during this study closed premises were visited three times, it was only possible to inspect 69% of the premises and the role of the unsurveyed premises regarding Ae.…”
Section: Container Categorymentioning
confidence: 98%
“…urban studies 4,5,9,10 . In two cities in Argentina, entomological indices were higher than in Puerto Iguazú (HI: 67-76%; CI: 18-39%; BI: 127-249) 9,10 .…”
Section: Container Categorymentioning
confidence: 99%
“…Carbajo et al (2006) reported the ready adaptation of this vector species to urban areas. Gürtler et al (2009) andFisher &Schweigmann (2010) noted the effects of vegetation, shade conditions, improperly maintained swimming pools, and housing and waste management in areas with high human densities as factors that maintain high infestation levels of mosquito vectors, including Ae. aegypti.…”
Section: Seasonal Oviposition Activity Ofmentioning
confidence: 99%